Virtual nation insights into contemporary Philippines - Mayuga, Sylvia L. (University of the Philippines Press, 2013)
Virtual Nation explores "a new way of being nation that Filipinos at home and all over the world are creating in cyberspace," as it contends that Filipinos are "still creating the nation our revolutionary forefathers envision and died for." Most of the essays in this book are opinion columns originally written for online publication from 2003 to 2010. In those seven turbulent years, major global challenges to peace and survival in the threefold crises of our time -- ecological, economic, and spiritual -- converged. That they emerged under the troubled Gloria Macapagal Arroyo presidency, coeval with the war-torn, terror-laden George W. Bush years, became a double spur to publish this book of "breaking history."